Loss of Hindustan : the invention of India - Asif, Manan Ahmed (Cambridge: Harvard University Press, 2020)
"The Loss of Hindustan presents a radical re-interpretation of how Europe came to see "India," and how "India" re-imagined history and in the process lost its identity of Hindustan as a home for all faiths. Asif uses Persian, Urdu, Sanskrit, English, French, Portuguese, and German histories about the subcontinent to demonstrate the work of history writing in the subcontinent before European rule, and how the practice of history writing changed as a result of colonialism. Turning back to the subcontinent's medieval past, the author focuses on the monumental history of Hindustan by Firishta, "Tarikh-i Firishta" which was written ca 1608 CE in the central, Deccan, region of the subcontinent. Firishta became the key source for European philosophers (Voltaire, Kant, Hegel) and historians (Edward Gibbon, James Mill) in the eighteenth and nineteenth century"--
Introduction: The end of Hindustan -- The question of Hindustan -- An archive for Hindustan -- The places in Hindustan -- The peoples in Hindustan -- A history for Hindustan.
Includes bibliographical references and index.
Keywords: Nationalism -- India -- History; Europeans -- Attitudes -- History; India -- Historiography; India -- Public opinion -- History